A influência das capacidades dinâmicas no processo de escalabilidade da inovação social - Pirotti, Tatiane Martins Cruz (Universidade do Vale do Rio dos Sinos, 2018)
Social innovations are important tools for minimizing or solving social problems. However, there are still major challenges regarding the management of social innovations development in order to expand their social impacts, thus generating what is meant by scalability. The dynamic capabilities and its microfoundations, if adapted to the social context, can serve as a support for the scalability process. By conducting a single case study in a Brazilian social innovation with more than four decades of existence, the present study analyzes in which ways the dynamic capabilities can influence the scalability process of a social innovation. The research method used is qualitative, using the process approach. The data were collected through interviews, documents and observations, which allowed to identify the existence of four methodological phases. The dynamic capabilities events and microfoundations that most impacted the process of scalability of the studied social innovation were listed and analyzed for each of these events. As main results, it was inferred that dynamic capabilities exert a positive influence on the scalability process of social innovation, aiding in the perception of opportunities and threats, as well as in the appropriation and creation of the transformations and adaptations necessary for environmental changes and scalability goals. In addition, it is understood that the emergence of new microfoundations is associated with the environmental needs, as well as the engagement of several actors. With this research, we aim to contribute to the management of social innovation, by listing practices (microfoundations) capable of influencing the scalability process. As a theoretical and academic contribution, the study advances the understanding of how dynamic capabilities can influence the scalability process, in addition to using the process research approach, which provided a deep understanding of the scalability process along the social innovation trajectory studied.
Keywords: Inovação social; Capacidades dinâmicas; Microprocessos; Escalabilidade; Social innovation; Dynamic capabilities; Microfoundations; Scalability; ACCNPQ::Ciências Sociais Aplicadas::Administração